2023
DOI: 10.3389/fmats.2023.1242507
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and recyclable thermosets with performances for high technology sectors. An environmental friendly alternative to toxic derivatives

Abstract: This study focuses on the development of environmentally friendly and chemically recyclable thermosets using or a renewable based monomer, the triglycidyl ether of phloroglucinol (TGPh), or a commercial non-toxic tris(4-hydroxyphenyl) methane triglycidyl ether (THPMTGE) monomer. The recyclable polyester thermosets were prepared by crosslinking the two monomers with hexahydro-4-methylphthalic anhydride (HMPA) or methyl nadic anhydride The TGPh-based formulations exhibited lower reaction temperatures and narrowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Among those investigated in that work, the most promising film had a tensile strength of 166 MPa, a fracture strain of 2.4%, and Young's modulus of 7.6 GPa. Dinu et al (2023) developed thermosets that were environmentally friendly and chemically recyclable using the triglycidyl ether of phloroglucinol (TGPh), a renewable-based monomer, or a commercial non-toxic tris(4-hydroxyphenyl) methane triglycidyl ether (THPMTGE) monomer. The physicochemical and thermomechanical properties of the developed resins were characterised by means of differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), hardness tests, tensile testing, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), among other techniques.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those investigated in that work, the most promising film had a tensile strength of 166 MPa, a fracture strain of 2.4%, and Young's modulus of 7.6 GPa. Dinu et al (2023) developed thermosets that were environmentally friendly and chemically recyclable using the triglycidyl ether of phloroglucinol (TGPh), a renewable-based monomer, or a commercial non-toxic tris(4-hydroxyphenyl) methane triglycidyl ether (THPMTGE) monomer. The physicochemical and thermomechanical properties of the developed resins were characterised by means of differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), hardness tests, tensile testing, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), among other techniques.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In this section, polymer-based materials such as thermosets are also included. Dinu et al (2023) reported the outstanding preparation of sustainable and recyclable thermosets which were synthesized by crosslinking triglycidyl ether of phloroglucinol (TGPh) with either hexahydro-4-methylphthalic anhydride (HMPA) or methyl nadic anhydride (MNA).…”
Section: D Carbon Materials Derived From Polymersmentioning
confidence: 99%
“…23,24 Resin formulations using epoxidized phloroglucinol (phloroglucinol trisepoxy, PHTE) in the presence of anhydride hardeners have been reported by Mija and colleagues, whereas they further pursued carbon fibre-reinforced polymer composite formation using a PHTE-based resin with ester bonds exhibiting recyclability (the matrix dissolved in ethylene glycol solution at 170 °C after 2.5 h). 25,26…”
mentioning
confidence: 99%